Color Stability of Gelamai With Added Oxygen Absorber During Shelf Life - Firmansyah Firmansyah; Laili Susanti; Syafnil Syafnil (Jurnal Teknologi Agro-Industri, 2025)
This study aims to analyze the effect of oxygen absorber on the color stability of gelamai. It evaluates changes in chroma and hue angle using the CIE Lab color system under two types of packaging (PE and vacuum) and two storage temperatures (room temperature and freezer) during 8 days. The colour changes observed in the samples were caused by oxidation. Throughout storage, the oxygen absorber reduces or retardes oxidative reactions. These findings revealed that vacuum packaging slowed colour changes more effectively than PE packaging, especially at room temperature, while freezer storage produced more complex and nonlinear patterns, likely due to physicochemical interactions. Kinetic analysis disclosed a difference in reaction rate constants (k) between packaging and temperature conditions, vacuum packaging disclosed lower kinetic value and more stable color than other conditions. PE room temp (R² = 0.9311), Vacuum room temp (R² = 0.5776), PE freezer (R² = 0.5847), Vacuum freezer (R² = 0.7258). Statistically disclosed no significant difference in all treatments. This study concludes that oxygen absorbers are effective in preserving the color quality of gelamai during storage.